An architectural approach to instructional design - Gibbons, Andrew S. (New York : Routledge, 2014)
"An Architectural Approach to Instructional Design is organized around a groundbreaking new way of conceptualizing instructional design practice. Both practical and theoretically sound, this approach is drawn from current international trends in architectural, digital, and industrial design, and focuses on the structural and functional properties of the artifact being designed rather than the processes used to design it. Harmonious with existing systematic design models, the architectural approach expands the scope of design discourse by introducing new depth into the conversation and merging current knowledge with proven systematic techniques. An architectural approach is the natural result of increasing technological complexity and escalating user expectations. As the complexity of design problems increases, specialties evolve their own design languages, theories, processes, tools, literature, organizations, and standards. An Architectural Approach to Instructional Design describes the implications for theory and practice, providing a powerful and commercially relevant introduction for all students of instructional design"--
part I. Fundamentals -- part II. Design in layers -- part III. The designer's value-added.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Instructional systems -- Design; Electronic books